Circle-to-circle amplification for precise and sensitive DNA analysis - Dahl, Fredrik (National Academy of Sciences, 2004)
We present a tightly controlled process for strand-specific amplification of circularized DNA molecules. Tandem repeated complements of DNA circles are generated by rolling-circle replication, and converted to monomer circles of opposite polarity to that of the starting material. These circles are then subjected to one more round of rolling-circle replication and circularization, and the process can be further repeated. The method can be directed to produce single-stranded circular or linear monomers, or linear concatemers of the desired polarity. The reaction is not product inhibited, and can yield ≈100-fold higher concentrations of monomer products than PCR. Each generation of the amplification process proceeds in a linear fashion, ensuring precise quantification. The procedure is suitable for parallel amplification of large numbers of DNA circles, because the few cycles and the robust reaction mechanism preserves the proportion of amplified molecules. We demonstrate the utility of the method for multiplexed genotyping of polymorphic loci and for quantitative DNA analysis.